2017
DOI: 10.3390/computation5010017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil-Structure Interaction on the Seismic Response of Liquid Storage Tanks under Earthquake Ground Motions

Abstract: Soil-structure interaction (SSI) could affect the seismic response of structures. Since liquid storage tanks are vital structures and must continue their operation under severe earthquakes, their seismic behavior should be studied. Accordingly, the seismic response of two types of steel liquid storage tanks (namely, broad and slender, with aspect ratios of height to radius equal to 0.6 and 1.85) founded on half-space soil is scrutinized under different earthquake ground motions. For a better comparison, the si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…The cone model generally used to determine the values of the rheological models considered in the modeling of subdomain by the substructures method. In this model, the components of the displacement field will vary along the depth in the shape of a truncated cone, as shown in Figure 3, for the horizontal translational degree of freedom [8].…”
Section: Cone Methodsmentioning
confidence: 99%
“…The cone model generally used to determine the values of the rheological models considered in the modeling of subdomain by the substructures method. In this model, the components of the displacement field will vary along the depth in the shape of a truncated cone, as shown in Figure 3, for the horizontal translational degree of freedom [8].…”
Section: Cone Methodsmentioning
confidence: 99%
“…Nghiên cứu của Seleemah [4], Rawat [5] và Tsipianitis [6] thực hiện với mô hình cô lập móng của bể chứa chất lỏng khỏi nền đất. Một số tác giả khác đã thực hiện nghiên cứu ứng xử của hệ bể chứa-chất lỏng dưới tải trọng động đất có xét đến biến dạng nền, nhưng là bài toán tuyến tính như: Larkin [7] nghiên cứu trên mô hình giản đơn 2 bậc tự do, chuyển vị ngang và góc xoay; Larkin [8] bổ sung bậc tự do theo phương đứng; Farajian [9] thay thế hệ đất nền-móng bằng mô hình giản đơn có dạng khối lượng-lò xo, chỉ xét đến bậc tự do nằm ngang của phương pháp hình côn (cone method). Bakalis [10] thực hiện nghiên cứu theo hướng mới, xét đến phi tuyến hình học (móng nhổ khỏi mặt tiếp xúc với đất), bằng phương pháp phần tử hữu hạn.…”
Section: Giới Thiệuunclassified
“…Ba bậc tự do theo phương ngang ( , , ) tương ứng với khối lượng , và khối lượng móng , có phương trình vi phân chuyển động (4)-( 6); bậc tự do góc xoay ( ) có phương trình vi phân chuyển động (7); và bậc tự do theo phương thẳng đứng ( ) có phương trình vi phân chuyển động (8). Hệ phương trình vi phân chuyển động (4)-( 8) viết dưới dạng véc-tơ như phương trình (9).…”
Section: Mô Hình Hệ Bể Chứa-chất Lỏng Xét đếN Ssiunclassified
See 1 more Smart Citation
“…For more than four decades, a wide variety of studies have been conducted to develop various base isolation devices and to study their effects on the improvement of the seismic performance of steel tanks [8][9][10][11][12][13][14]. However, several factors influence the seismic responses of structures [15,16], and in the case of base-isolated liquid storage tanks, they may have adverse effects leading to an increase in seismic demands compared to the fixed base condition [17][18][19]. For example, Bagheri and Farajian [17] showed that the base isolation may experience an excessive displacement when the system is subjected to near-fault excitations with severe pulses, resulting in a dramatic increase in the displacement of the impulsive mass and, consequently, base shear and overturning moment.…”
Section: Introductionmentioning
confidence: 99%